2018
DOI: 10.1111/dme.13580
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal experiences, knowledge and perceptions of women with gestational diabetes

Abstract: This study has suggested potential avenues to be explored in terms of content, timing and potential recipients of interventions. Educational interventions postnatally could address illness perceptions in women with GDM and redress the situation where lack of aftercare downplays its seriousness. For lifestyle interventions, the child's health could be used as a motivator within the context of later joint or family interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 14 publications
3
44
0
Order By: Relevance
“…This demonstrates a seemingly mutually beneficial relationship through which the women received motivation to eat healthy and be more physically active, while modelling and engaging children in these behaviours. Motivation for behaviour change due to concern for their child's health was also reflected in a recent study that found women made dietary and physical activity changes to protect the health of their unborn child (Eades et al, 2018). Thus, there may be some merit in finding ways to include children in behaviour change initiatives, which might alleviate the barrier of childcare, and promote a healthier lifestyle for both parties (Rosal et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This demonstrates a seemingly mutually beneficial relationship through which the women received motivation to eat healthy and be more physically active, while modelling and engaging children in these behaviours. Motivation for behaviour change due to concern for their child's health was also reflected in a recent study that found women made dietary and physical activity changes to protect the health of their unborn child (Eades et al, 2018). Thus, there may be some merit in finding ways to include children in behaviour change initiatives, which might alleviate the barrier of childcare, and promote a healthier lifestyle for both parties (Rosal et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The studies reflected a variety of sampling methods and data collection methods. For example, interviews were conducted in 34 studies [10, 12, 13, 25, 27, 28, 30-32, 34-36, 38-50, 52-58, 60, 61], focus group methods were used in three [19,32,37], and interviews and focus groups were used in two studies [29,51]. Two studies used a mixed method approach [26,59].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…'[58] 'GDM was a hidden blessing for me... GDM can go away after you have the baby but diabetes is not so easily fixable …I am much more aware of [the] need to prevent it. '[32] 'It's also good with my diabetes diet I ended up weighing pretty much the same at the end of the pregnancy as I did at the beginning. '[31]…”
mentioning
confidence: 99%
“…The TPB is widely used to explain the associations between intentions to eat a between healthy diet and adherence behavior [ 17 , 18 ]. Eades and colleagues conducted a study using semi-structured interviews according to the TPB [ 19 ]. Their finding revealed that changing the diet was the first choice related to lifestyle changes during and after pregnancy among women with GDM; this practice was most commonly motivated by instrumental attitude, such as concern for the fetus and the desire to avoid taking medication to treat GDM.…”
Section: Introductionmentioning
confidence: 99%